Screen Time, Age and Sunshine Duration Rather Than Outdoor Activity Time Are Related to Nutritional Vitamin D Status in Children With ASD - Shan, Ling; Dong, Hanyu; Wang, Tiantian; Feng, Junyan; Jia, Feiyong (Frontiers in Pediatrics, 2022)
Objective: This study aimed to investigate the possible association among vitamin D, screen time and other factors that might affect the concentration of vitamin D in children with autism spectrum disorder (ASD). Methods: In total, 306 children with ASD were recruited, and data, including their age, sex, height, weight, screen time, time of outdoor activity, ASD symptoms (including Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS) and Autism Diagnostic Observation Schedule–Second Edition (ADOS-2)) and vitamin D concentrations, were collected. A multiple linear regression model was used to analyze the factors related to the vitamin D concentration. Results: A multiple linear regression analysis showed that screen time (β=-0.122, P=0.032), age (β=-0.233, P＜0.001), and blood collection month (reflecting sunshine duration) (β=0.177, P=0.004) were statistically significant. The vitamin D concentration in the children with ASD was negatively correlated with screen time and age and positively correlated with sunshine duration. Conclusion: The vitamin D levels in children with ASD are related to electronic screen time, age and sunshine duration. Since age and season are uncontrollable, identifying the length of screen time in children with ASD could provide a basis for the clinical management of their vitamin D nutritional status.